Actions with economic elements embedded in the social networks of Danish farmer investors abroad - Luljeta Hajderllari (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
The main aim of this paper is to investigate the "embeddedness" of business relationships with social relationships of Danish farmer investors (DFI) concerning agricultural investment and expansion abroad. A survey was sent to 61 DFIs with activities in Central and Eastern European countries who are members of an organisation named Danish Farmers Abroad. The survey elicited information regarding their organisational network connections to other DFIs who also have activities abroad. Information about the DFIs' network was obtained regarding their business relationships (cooperation, competition and advice given and received to and from other DFIs) and social relationships (friendship). The data of the four different networks was analysed by the Double Dekker Semi-Partialling Multiple Regression Quadratic Assignment Procedure in UCINET. The results indicate that cooperation as well as received and given advice are positively related to social ties, whereas competition is negatively related to social ties. These results support the idea that business relationships (with the exception of competition) of DFIs are embedded in social relationships. This indicates that the same actors may behave less cooperatively in environments with low trust where they have to compete for scarce resources.
Keywords: M14; L22; 330; Embeddedness; social network analysis; Danish farmer investors